Indoor air quality – An overview of methods for measuring odor detection thresholds of single substances - Thiele, Vanessa; Monsé, Christinan; Hoffmeyer, Frank; Brüning, Thomas; Bünger, Jürgen; Sucker, Kirsten (Respiratory physiology & neurobiology, 2023)
Odor evaluation is an important topic in the field of indoor air quality. Odor detection threshold (ODT) values are used to derive limit values like odor guide values or odor activity value. However, ODT values for the same substance available in compilations or published before 2003 rarely have an accuracy of less than three orders of magnitude. Stimulus preparation, including analytical verification, stimulus presentation, as well as selection and training of test subjects have been identified as major sources of variability. ODT values obtained by validated standardized methods are now considered objective, reliable, and reproducible. They exhibit a variability of one or two orders of magnitude and are lower than traditionally assumed and reported.This review presents the essential criteria for a well-performed ODT determination. It is intended to assist health and safety professionals in assessing whether the methodological approach of a study was appropriate for determining a valid and reliable ODT value. •Reliable and valid odor detection threshold values are needed to establish limit values for indoor air pollutants, such as odor guide values or odor activity value.•Odor detection threshold values published in compilations rarely have an accuracy of less than 1000%.•The review provides health and safety professionals with criteria for evaluating the quality of published odor detection threshold values.